2004
DOI: 10.1158/1078-0432.ccr-0842-03
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics of Weekly and Every-Three-Weeks Docetaxel

Abstract: Purpose: Weekly administration of docetaxel has demonstrated comparable efficacy together with a distinct toxicity profile with reduced myelosuppression, although pharmacokinetic data with weekly regimens are lacking. The comparative pharmacokinetics of docetaxel during weekly and once every 3 weeks (3-weekly) administration schedules were evaluated.Experimental

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 49 publications
4
99
0
Order By: Relevance
“…Docetaxel PK parameters were consistent with those reported historically despite the co-administration of ispinesib (Figure 2; Baker et al, 2003). …”
Section: Pharmacokineticssupporting
confidence: 84%
See 1 more Smart Citation
“…Docetaxel PK parameters were consistent with those reported historically despite the co-administration of ispinesib (Figure 2; Baker et al, 2003). …”
Section: Pharmacokineticssupporting
confidence: 84%
“…Using a validated population model, observed ispinesib concentration -time data from this study were overlaid on the simulated profile. Observed docetaxel data from subjects in this study administered 60 and 75 mg m À2 were overlaid with historical data from subjects dosed with 35, 75 and 100 mg m À2 docetaxel (Baker et al, 2003) to ascertain if an interaction was observed affecting docetaxel concentration -time profiles.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Consistent with this hypothesis is some evidence showing that the level of circulating docetaxel in the first course of treatment is positively related to the time to progression in non-small cell lung cancer patients (20). Since the level was typically reduced to the low nanomolar range by one week after dose administration, docetaxel may have caused a persistent reduction of dynamicity (21). However, the evidence does not suggest that higher dosages of depolymerizing drugs, which affect microtubule integrity rather than dynamicity, are less effective therapeutically (see Discussion).…”
Section: Introductionmentioning
confidence: 69%
“…The differences described here may have clinical implications, providing a rational approach to lower the therapeutic concentrations of docetaxel-based chemotherapy. In this sense, at the clinical setting, it has been shown that weekly regimen of docetaxel (with lower concentrations of drug) can achieve a clinical response comparable to traditional 3-weekly regimens (with higher concentrations of drug), although the side effects profile is improved (Baker et al, 2004). In addition, the cytotoxicity of docetaxel mediated by mechanisms alternative to apoptosis may be partly responsible for their efficacy in treating breast cancers, which may be apoptosis deficient.…”
Section: Discussionmentioning
confidence: 99%